PENGARUH PELATIHAN MEMBACA EFEKTIF TERHADAP PENINGKATAN KECEPATAN MEMBACA DAN PEMAHAMAN BACAAN - Arih Merdekasari (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2015)
Adolescents’ reading ability is required in academic achievement and socialization. Speed reading and reading comprehension required so that adolescents can gather information to make the right decisions in their life. The fact that adolescent literacy education in secondary schools is still inadequate. Has not shown much effort to fix it so necessary an effective reading training to improve the speed reading and reading comprehension. This study aimed to test whether effective reading training can improve  speed reading and reading comprehension. Hipotesis are effective reading training can improve speed reading and reading comprehension. The Selection subject of research at students' academic achievement. Categorized in groups of student achievement are very good, good, average, below average and bad. Training participants were 20 students in the seventh grade SMPN1 Kasreman taken at random technique. Namely, 4 students in each category of academic achievement group. From the analysis of data obtained through the Wilcoxon test  Z = -3, 993 with a significance level 0.00 on speed reading scores. While the Wilcoxon test  Z = 3, 271 with a significance level of 0.001 on reading comprehension scores. This means that there are significant differences in speed reading and comprehension reading  scores before effective reading training and after effective reading training. Based on the results of the study concluded that Effective reading training can improve speed reading and comprehensive reading.Adolescents’ reading ability is required in academic achievement and socialization. Speed reading and reading comprehension required so that adolescents can gather information to make the right decisions in their life. The fact that adolescent literacy education in secondary schools is still inadequate. Has not shown much effort to fix it so necessary an effective reading training to improve the speed reading and reading comprehension. This study aimed to test whether effective reading training can improve  speed reading and reading comprehension. Hipotesis are effective reading training can improve speed reading and reading comprehension. The Selection subject of research at students' academic achievement. Categorized in groups of student achievement are very good, good, average, below average and bad. Training participants were 20 students in the seventh grade SMPN1 Kasreman taken at random technique. Namely, 4 students in each category of academic achievement group. From the analysis of data obtained through the Wilcoxon test  Z = -3, 993 with a significance level 0.00 on speed reading scores. While the Wilcoxon test  Z = 3, 271 with a significance level of 0.001 on reading comprehension scores. This means that there are significant differences in speed reading and comprehension reading  scores before effective reading training and after effective reading training. Based on the results of the study concluded that Effective reading training can improve speed reading and comprehensive reading.